The Adventures of a Country Boy at a Country Fair - Otis, James, 1848-1912 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Adventures of a Country Boy at a Country Fair" by James Otis is a children's novel written in the late 19th century. The story revolves around a young boy named Teddy Hargreaves who dreams of running his own booth at the local fair to help pay off his family$1 (Bs debts. Throughout the narrative, Teddy navigates the challenges of entrepreneurship, friendships, and encounters with dubious characters. At the start of the story, Teddy expresses excitement about running a cane and knife board at the Peach Bottom fair, eagerly seeking financial help from his Uncle Nathan. Despite initial skepticism from his family, Teddy is determined to succeed. However, his plans quickly unravel when he becomes embroiled in a more complex situation involving a thief and a con artist who steals his money. As the story unfolds, Teddy illustrates his bravery and resourcefulness, ultimately striving to clear his name while helping others, setting the stage for a series of adventures that blend both humor and wit. (This is an automatically generated summary.)s
Release date is 2011-10-06
E-text prepared by Juliet Sutherland, Matthew Wheaton, and the Online Distributed Proofreading Team
Keywords: Conduct of life -- Juvenile fiction; Children -- Conduct of life -- Juvenile fiction; Friendship -- Juvenile fiction; Agricultural exhibitions -- Juvenile fiction; Country life -- Juvenile fiction; Uncles -- Juvenile fiction; Escapes -- Juvenile fiction; Clergy -- Juvenile fiction; Theft -- Juvenile fiction; Prisoners -- Juvenile fiction; Intergenerational relations -- Juvenile fiction; Burglars -- Juvenile fiction; Debt -- Juvenile fiction; Fairs -- Juvenile fiction; Fakirs -- Juvenile fiction